Water‐soluble food dye of Allura Red as a tracer to determine the spray deposition of pesticide on target crops. Issue 10 (25th April 2019) - Gao, Saichao; Wang, Guobin; Zhou, Yangyang; Wang, Ming; Yang, Daibin; Yuan, Huizhu; Yan, Xiaojing
Abstract: BACKGROUND: Quantification of spray deposition on a target crop is of vital importance to optimize pesticide application. In traditional determinations of spray deposition, a large amount of organic solvent is used to extract pesticides from the target crops. In this study, a water‐soluble food dye of Allura Red was developed as a tracer to determine pesticide spray deposition on a rice target crop. RESULTS: The addition of Allura Red does not obviously alter the physicochemical properties of pesticides (viscosity, density and surface tension) and droplet spectra. An ultra‐performance liquid chromatography (UPLC) analytical method was developed and validated to determine the deposition amount of Allura Red on rice plants. Method accuracy and precision for Allura Red were found to be satisfactory with recoveries of 96.07% to 107.48%. To validate the method, comparative deposition analyses were carried out using representative systematic and non‐systematic pesticides (nitenpyram and chlorothalonil) under the same spraying scenarios using a Potter spray tower. Allura Red and pesticides showed comparable deposition under the same application conditions with ratios from 0.98 to 1.21. A field trial using an unmanned aerial vehicle sprayer further indicated that the deposition rates for Allura Red and nitenpyram on rice seedling were 13.04% and 11.07%, with corresponding relative standard deviation values ( n = 5) of 16.39% and 18.79%. CONCLUSION: A laboratory test and field trial confirmed that the developed method of using Allura Red as a tracer for spray deposition assessment is feasible and practicable. © 2019 Society of Chemical Industry Abstract : Allura Red as a tracer to determine the deposition of pesticide.